Strongly Rickart Modules - Arif, Tamadher; Al-Saadi, Saad Abdulkadhim (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we introduce and study the concept of strongly Rickart modules and strongly CS-Rickart modules as a stronger than of Rickart modules [8] and CS-Rickart modules[3] respectively. A module M is said to be strongly Rickart module if the right annihilators of each single element in S = EndR(M) is generated by a left semicentral idempotent in S. A module M is said to be strongly CS- Rickart if for any ??S, rM(?) is an essential in fully invariant direct summand of M. Properties, results, characterizations and relation of these concepts with others known concepts of modules are studied.